An introduction to strategic management concepts and cases - David, Fred R. (Pearson Education South Asia Pte Ltd, 2007)
The eleventh edition of Strategic Management is a current, well-written strategic management book with the most up-to-date compilation of cases available. The author provides an overview of strategic management, as well as strategy formulation and implementation, strategy evaluation, strategic management case analysis. For management professionals, small business owners and others involved in business.